CHILDREN BORN BY HIV POSITIVE MOTHERS. WAYS OF IMPROVEMENT OF MEDICAL AND SOCIAL AID - V.N. Sadovnikova; O.V. Chumakova; N.V. Vartapetova; A.V. Karpushkina ("Paediatrician" Publishers LLC, 2008)
Results of complex research aimed at the study of dynamics of incidence and mortality caused by human immunodeficiency virus (HIV) among children, their medical and social characteristics, problems of social adaptation of rejected children, are presented. It is shown that in the dynamics of HIV incidence among children a steady growth trend is observed, mostly due to children born by HIV positive mothers. The number of HIV positive children due to perinatal transmission, increased by 9 times in 2000-2006. 43,6 per cent of children born by HIV positive mothers had significant deviations in the health status, 21,6 percent of infants were transferred to the 2nd stage of nursing. High level of stillbirths, perinatal and early neonatal mortality of infants born by HIV positive mothers, was observed. Though there is a certain trend of decreasing the number of rejected children both in the general population and among HIV positive mothers, the absolute number of such cases is increasing in the latter group. Children abandoned by their parents in most cases are isolated and do not receive the necessary social and psychological aid. Key words: HIV infection, children, perinatal mortality, social adaptation.